Waterwheels and Steam Engines in Ontario: Industrial Power Reported in the 1871 Manuscript Census - Bloomfield, Gerald; Bloomfield, Elizabeth (Scientia Canadensis, 1989)
ABSTRACTThe transition from water to steam power has long been an interesting issue in the history of technology. Newly created data for the 1871 manuscript census are used to examine features of the transition in Ontario. Industrial characteristics and geographical variations of each power source are discussed. Questions and implications for further research are explored in relation to contemporary work environments and power technology.